Psychosocial impact of COVID-19 on achievement of adolescents with hearing impairment in English language - Samuel Olufemi Adeniyi; Olaotan Oladele Kuku (JOALL (Journal of Applied Linguistics and Literature), 2023)
This study examined psychosocial impact of Covid-19 on the achievement of secondary school adolescents with hearing disabilities in English Language in Lagos State. A survey research design was employed with population of hearing-impaired adolescents. A sample of hundred adolescents with hearing impairment was selected for the study using purposive sampling technique to select the participants and simple random sampling to select four schools practicing inclusion. The instruments for data collection were ELAT (English Language Achievement Test) and Psychosocial Scale (PSS) with reliabilities of 0.69 and 0.79 respectively. Pearson Product Moment Correlation Coefficient and Multiple Regression were used to analyse data collected. The hypotheses formulated were tested at 0.05 level of significance. The results of the four hypotheses tested revealed that aggression, self-esteem and communication have positive relationship to the academic achievement of the hearing-impaired adolescents in English Language as a result of Covid-19. Further findings discovered that there was a combined effect of aggression, self-esteem and communication on academic performance of secondary school adolescents with hearing impairment in English Language. Therefore, teaching methodology should be more of cooperative learning approach to motivate sense of belongings and friendliness of adolescents with hearing impairment in Lagos State.